2017
DOI: 10.1080/09638288.2017.1300340
|View full text |Cite
|
Sign up to set email alerts
|

“That is how I speak nowadays” – experiences of remote communication among persons with communicative and cognitive disabilities

Abstract: Better access to remote communication trough assistive technology such as speech synthesis and picture symbols would make remote communication easier and facilitate participation for people with communicative and cognitive disabilities. Implications for rehabilitation People with communicative and cognitive disabilities face challenges with access to remote communication. Access to communication technology including remote communication is important for self-determination, for personal safety and for overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 33 publications
3
23
0
13
Order By: Relevance
“…The participants describe the importance of functioning remote communication for safety issues which is in line with the results of a previous study [14]. Buchholz et al [3] interviewed persons with communicative and cognitive disabilities and results showed that only a few had managed to ask for help by using remote communication. This is alarming in terms of safety.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The participants describe the importance of functioning remote communication for safety issues which is in line with the results of a previous study [14]. Buchholz et al [3] interviewed persons with communicative and cognitive disabilities and results showed that only a few had managed to ask for help by using remote communication. This is alarming in terms of safety.…”
Section: Discussionsupporting
confidence: 83%
“…Managing independent remote communication can make a difference regarding the possibility to develop social contacts, meaningful activities and interests, and a meaning in life. Independent remote communication becomes more important in the transition to adulthood which was also found in a previous study [3]. The finding that remote communication can compensate for physical, cognitive, and social limitations has also been described by others.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations